Prospective nursing care certification using the 25‐question Geriatric Locomotive Function Scale. Issue 6 (13th April 2021) - Ide, Koichiro; Yamato, Yu; Hasegawa, Tomohiko; Yoshida, Go; Yasuda, Tatsuya; Banno, Tomohiro; Arima, Hideyuki; Oe, Shin; Mihara, Yuki; Ushirozako, Hiroki; Yamada, Tomohiro; Watanabe, Yuh; et al.
Abstract : Aim: The 25‐question Geriatric Locomotive Function Scale (hereafter, "GLFS‐25") is a simple screening tool to detect elderly individuals at high risk of locomotive syndrome and promote interventions. This cohort study aimed to clarify if it can predict the need for nursing care certification in the near future. Methods: Participants were 531 Japanese adults aged ≥65 years who had undergone a healthcare checkup in 2012 and never received nursing care certification until 2012. We collected baseline information and conducted a physical examination in 2012. We investigated the presence of nursing care certification and care need level from 2013 to 2018. Relationships of these factors with nursing care certification after 6 years were assessed. A receiver operating characteristic curve for both the GLFS‐25 and physical examination were used to determine optimal threshold value. Results: From 2013 to 2018, 114 volunteers (21.4%) applied for nursing care certification and 29 volunteers died. The group with nursing care certification (over support level 1) had an average age of 79.9 years and a mean score of 17.8 on the scale. Those without nursing care certification had an average age of 74.1 years and a mean score of 8.7. When the GLFS‐25 score was 12.5, sensitivity was 0.658 and specificity was 0.760. The area under the curve was 0.736 (95% confidence interval 0.682–0.789). Conclusions: The GLFS‐25 has enabled early detection of individuals with locomotive syndrome who are more likely to need nursing care certification in the near future. We propose using a cutoff score of 13 for the scale. Geriatr Gerontol Int 2021; 21: 492–497 .